Bibliometric and Visual Analysis of Alzheimer’s Disease and Herpes Simplex Virus Type 1 Infection Between 1990 and 2024 - Ren H; Song R; Wang H; Zeng Q; Fu Y; Guo Y; Xie Y; Ge Y (Journal of Multidisciplinary Healthcare)
Hongling Ren,1 Ruiyao Song,1 Hairong Wang,1 Qingyan Zeng,1 Yu Fu,1 Yunchu Guo,1 Ying Xie,2 Yusong Ge1 1The Department of Neurology, the second Affiliated Hospital of Dalian Medical University, Dalian City, Liaoning Province, 116023, People’s Republic of China; 2The Department of Infection Control and Prevention, the second Affiliated Hospital of Dalian Medical University, Dalian City, Liaoning Province, 116023, People’s Republic of ChinaCorrespondence: Yusong Ge; Ying Xie, The second Hospital of Dalian Medical University, No. 467 Zhongshan Road, Shahekou District, Dalian City, Liaoning Province, 116023, People’s Republic of China, Tel +86-17709873200 ; +86-17709877781, Email geyusongmed@dmu.edu.cn; 936135710@qq.comBackground: Recently, some studies suggested that Herpes simplex virus type 1 (HSV-1) infection is an important environmental factor for Alzheimer’s disease(AD). The literature on research about HSV-1 infection and AD is emerging. This study used the bibliometric method to investigate the relationship between HSV-1 infection and AD.Methods: We searched the Web of Science Core Collection for relevant literature on AD and HSV-1 from 1990 to 2024. Bibliometric and visualization analyses were performed using VOSviewer and CiteSpace.Results: From 1990 to 2024, the number of publications showed an increasing trend. The United States made the largest contributions in productivity. The University of Manchester was the most productive organization. Professor Ruth F. Itzhaki was the most influential researcher. The Journal of Alzheimer’s Disease had published the most articles. Research on the mechanisms by which HSV infection contributes to AD remains a hotspot in the field, and future studies may further focus on antiviral therapeutic strategies targeting HSV-1 infection.Conclusion: Our analysis provides basic information about research in AD and HSV-1. The current research hotspots in this field mainly include the mechanism of AD caused by HSV-1, and antiviral drugs to treat or prevent AD.Keywords: Alzheimer’s disease, Herpes simplex virus type 1, bibliometric, visualized analysis, VOSviewer, citespace